Repurposing Immunomodulatory Drugs to Combat Tuberculosis - Fatima, Samreen; Bhaskar, Ashima; Dwivedi, Ved Prakash (Frontiers in Immunology, 2021)
Tuberculosis (TB) is an infectious disease caused by an obligate intracellular pathogen, Mycobacterium tuberculosis (M.tb) and is responsible for the maximum number of deaths due to a single infectious agent. Current therapy for TB, Directly Observed Treatment Short-course (DOTS) comprises multiple antibiotics administered in combination for 6 months, which eliminates the bacteria and prevents the emergence of drug-resistance in patients if followed as prescribed. However, due to various limitations viz., severe toxicity, low efficacy and long duration; patients struggle to comply with the prescribed therapy, which leads to the development of drug resistance (DR). The emergence of resistance to various front-line anti-TB drugs urgently require the introduction of new TB drugs, to cure DR patients and to shorten the treatment course for both drug-susceptible and resistant populations of bacteria. However, the development of a novel drug regimen involving 2-3 new and effective drugs will require approximately 20-30 years and huge expenditure, as seen during the discovery of bedaquiline and delamanid. These limitations make the field of drug-repurposing indispensable and repurposing of pre-existing drugs licensed for other diseases has tremendous scope in anti-DR-TB therapy. These repurposed drugs target multiple pathways, thus reducing the risk of development of drug resistance. In this review, we have discussed some of the repurposed drugs which have shown very promising results against TB. The list includes sulphonamides, sulphanilamide, sulfadiazine, clofazimine, linezolid, amoxicillin/clavulanic acid, carbapenems, metformin, verapamil, fluoroquinolones, statins and NSAIDs and their mechanism of action with special emphasis on their immunomodulatory effects on the host to attain both host-directed and pathogen-targeted therapy. We have also focused on the studies involving the synergistic effect of these drugs with existing TB drugs in order to translate their potential as adjunct therapies against TB.